(3MeGjI GdedcjI GdacQjI aj GdbhGfjf GdhWfjI hGdOhdjI (B=s Intellectual property protection in national and international laws - (3QHjY, RjGO eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2020)
(3jJfGhd gPG GdcJGH GdJWhQ GdgGFd GdPj JTgOg GdHTQjI aj eLGd GdEHOGY GdacQj hGdUfGYj hGdJLGQj jJWdH hVY GdbhGYO GdbGfhfjI dEOGeI gPg GdEfLGRGJ GdEfSGfjI GdYXjeI hUjGfJgG hGdeMGaXI YdjgG hJWhjQgG heOgG HCSHGH JbOegG hGdMK Ydi JTLjY GdYbhd GdfjQI HCf JbOe eG dOjgG ef EfJGL eYQaI acQjI hYdejI hEfSGfjI hGHJcGQGJ hGNJQGYGJ dNOeI GdEfSGf hJWhjQ MjGJg, dgPG abO GJLgJ GdOhd HeNJda fRYGJgG GdSjGSjI hGdCjOhdhLjI Edi MeGjI GdeHOYjf hGdeNJQYjf GdPjf CSgehG aj SYGOI GdHTQjI hQbjgG hbO VefJ gPg GdbhGfjf MeGjI Mbhbge hefY GdJYOj YdjgG ef bHd GdBNQjfhSgdJ ENQGL EHOGYGJge hGHJcGQGJge heOJge HeG jVef MeGjI bGfhfjI LGOI JSge aj YOe GdJYQV dLghOge hefMge GdYOjO ef GdMbhb dJWhjQ EHOGYGJge hEfJGLge HTcd jLYdgG JJdGAe eY GdJWhQGJ GdJj JTgOgG TYhH GdYGde(B. (3hef CLd Pdc CUOQJ GdOhd GdYOjO ef GdbhGfjf dMeGjI GdEHOGYGJ GdacQjI efgG bhGfjf Mb GdeDda hGdeNJQY hGdEHOGYGJ GdNGUI GdJLGQjI hGdUfGYjI hGdEdcJQhfjI HeG jfSLe hJWdYGJ GdeLJeY GdHTQj(B. (3hGJLgJ GdYOjO ef GdLGeYGJ dJOQjS MeGjI GdedcjI GdacQjI aj GdcdjGJ GdeYfjI HGdOQGSGJ GdbGfhfjI hYdi GdQZe ef Cf GdTQjYI GdESdGejI GgJeJ HGdLGfH GdYdej hChdJ GdefaYI GdYGeI GdCgejI GdcHQi, EdG CfgG fXQJ Edi GdYdeGA GdeSdejf fXQI cHjQI hefMJge GdefRdI GdJj Jdjb Hge(B. (3aCUHM GdYdeGA GdeSdehf GdfhQ GdPj JgJOj Hg GdCeI GdESdGejI hJSJQTO HCacGQgG hef LgI CNQi de JLYd GdYde MbkG ef Mbhb GdEfSGf ceG gh aj GdbGfhf GdOhdj GdeYGUQ, EfeG LYdJ GdYde aQjVI Ydi cd eSde heSdeI(B.s
(3HHdjhLQGajI (B: (3UaMI (B375-384.s
Keywords: (3Mbhb GdJCdja hGdfTQs -- (3bhGfjf hJTQjYGJs; (3Mbhb GdJCdja hGdfTQ (B((3bGfhf Ohdj(B)s; (3Mbhb GdJCdja hGdfTQs -- (3bhGfjf hJTQjYGJs -- (3MeGjIs; (3GdedcjI GdUfGYjIs -- (3bhGfjf hJTQjYGJs; (3HQGAGJ GdGNJQGYs -- (3bhGfjf hJTQjYGJs; (3GdYdGeGJ GdJLGQjIs -- (3bhGfjf hJTQjYGJs; (3GdJYhjVGJs -- (3bhGfjf hJTQjYGJs